Foreign aid mix and manufactured exports performance in sub-Saharan Africa - Ndalama, Jewel Stebbins (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
This study aims at finding out effects of foreign aid mix on manufactured exports performance in Sub-Saharan Africa. This is important as the region has lagged behind on promotion of manufactured exports thereby relying on primary exports. For a country's exports to be competitive internationally, and hence improve economically, it has to manufacture products part of which can be exported. Sub-Saharan African countries have relied on primary exports which fetch low prices at international market thereby bringing in low foreign exchange. This is why African countries have relied on foreign aid since they cannot generate enough foreign exchange which is needed to import goods and services they cannot produce domestically. African countries have to boost manufactured exports which fetch high prices at international market hence they bring in the much-needed foreign exchange. Reliance on foreign aid may not be sustainable as donors have their own priorities and may not be able to give aid indefinitely. African countries have to find sustainable ways of generating foreign exchange one of which is to boost manufactured exports. As boosting manufactured exports in these countries requires resources, foreign aid can be used to improve manufacturing and manufactured exports. In this case, the countries can later stop relying on foreign aid. This study first examines the impact of foreign aid on terms of trade. Holding price of imports constant, improvement in terms of trade means that either prices of primary exports have increased or there has been improvement in manufactured exports which are known to fetch high prices at international market. The study then examines the impact of foreign aid on manufactured exports. Most of the studies have dwelt on the impact of foreign aid on exports. This study has gone further to assess the impact of foreign aid on one of the components of exports namely manufactured exports. Thereafter, the study examines the impact of disaggregated foreign aid on manufactured exports. While some studies have criticised foreign aid as having little or no impact on recipient country, it is necessary to disaggregate the aid by sector since aid to some sectors may have positive impact on those sectors, and other sectors of the economy. The study has also examined asymmetric effects of various types of foreign aid, that is, whether or not, positive and negative changes of each type of aid have the same impact on manufactured exports. The study uses both panel and pooled data for 30 Sub-Saharan African countries for the period from 1970 to 2019. Models used include Autoregressive Distributed Lag (ARDL), Non-linear Autoregressive Distributed Lag (NARDL), Generalised Least Squares (GLS), among other models. The study has found that foreign aid has a negative and statistically significant impact on terms of trade. This means that foreign aid does not improve export prices relative to those of imports in the Sub-Saharan African countries. According to Prebisch-Singer Dependency Theory, price of primary commodities declines relative to the price of manufactured goods, causing terms of trade of primary product-based economies to deteriorate. This study has shown that foreign aid deteriorates terms of trade thereby worsening the situation of African countries which mainly export primary commodities and import manufactured products. This calls for African economies to diversify their export base to include manufactured exports, otherwise, foreign aid, which is one of the main sources of resources for African economies will keep on worsening the countries' terms of trade. Further, the study finds that foreign aid has negative impact on manufactured exports. Like other studies that have disputed the impact of foreign aid on economic growth, this study has also found that foreign aid does not have a positive impact on manufactured exports, one of the most important factors influencing economic growth in any country. This calls for policy reform on building manufacturing capabilities in the Sub-Saharan African countries. Effectiveness of foreign aid also depends on dynamics of a country as country specific results show varying effects of foreign aid on manufactured exports, with some countries experiencing positive impact and others negative impact. Donors should therefore be assessing whether in the prospective recipient country, foreign aid will have a positive impact on manufactured exports especially if their aim is to boost manufactured exports. Though total aid has a negative and statistically insignificant impact on manufactured exports, disaggregating it shows that other types of aid such as grants, agricultural aid and health aid have positive and statistically significant impacts. Thus, criticising foreign aid is not proper as some of its components have positive impact on manufactured exports. Therefore, allocating foreign aid to sectors that can impact positively on manufactured exports will go a long way in boosting manufactured exports in these countries. In addition to assessing recipient countries, donors should assess sectors in each country to find out sectors which if funded can boost manufactured exports. Country-specific results show different impacts of different types of aid with some types having positive impact, and others negative impact on manufactured exports. This means that the effectiveness of different types of foreign aid depends on a country. The study has also shown that there are no asymmetric effects of all types of aid meaning that there are no significant differences in impacts of positive or negative changes in the types of aid. Fixed capital (proxy for infrastructure development), foreign direct investment, and openness are found to be positively related to manufactured exports and statistically significant regardless of model used, and whether data used is pooled or panel. This calls for other ways of improving manufactured exports in the region. Improving infrastructure (fixed capital), attracting foreign direct investment, and opening up Sub-Saharan African countries can go a long way in promoting manufactured exports in the region. The study also ran regressions after including private sector credit, and excluding Zimbabwe, a country that faced economic challenges during the study period especially towards the end of the study period to the extent that macroeconomic fundamentals were far from being normal. However, results are not much different from results without private sector credit, and inclusion of Zimbabwe.
Keywords: Manufactures; Economic assistance -- Africa, Sub-Saharan; Terms of trade; Comparative advantage (International trade); Heckscher-Ohlin principle; Free trade; Import substitution; Foreign trade promotion